Asset Turnover, Inventory Turnover, Dividend Policy and Profit Growth - Suhernah, Suhernah (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the effect of total asset turnover, inventory turnover, and dividend policy on profit growth. Total asset turnover is measured using the ratio between sales and total assets, inventory turnover is measured using the ratio between the cost of goods sold and average inventory, and dividend policy is measured using the dividend payout ratio (DPR), which compares dividends per share with earnings per share. Meanwhile, profit growth is measured by subtracting the current period's profit from the previous period's profit and dividing it by the previous period's profit. This study's population is healthcare sector companies listed on the Indonesia Stock Exchange for 2017-2021. The number of samples in this study was 7 companies obtained through purposive sampling and obtained sample data of 35 data. This study's data type is secondary data with quantitative research methods. The analysis technique used is panel data regression analysis with a significance level of 3%. This research was processed using Eviews 9 software. It showed that (1) Total Asset Turnover had a significant effect on Profit Growth, (2) Inventory Turnover had a significant effect on Profit Growth, and (3) Dividend Policy had no significant effect on Profit Growth.